Ionically Conductive Hydrogel with Fast Self‐Recovery and Low Residual Strain as Strain and Pressure Sensors. Issue 13 (5th June 2020) - Sun, Xia; Yao, Fanglian; Wang, Chenying; Qin, Zhihui; Zhang, Haitao; Yu, Qingyu; Zhang, Hong; Dong, Xiaoru; Wei, Yuping; Li, Junjie
Abstract: Hydrogel‐based sensors have attracted enormous interest due to their broad applications in wearable devices. However, existing hydrogel‐based sensors cannot integrate satisfying mechanical performances with excellent conductivity to meet the requirements for practical application. Herein, an ionically conductive hydrogel with high strength, fast self‐recovery, and low residual strain is constructed through a facile soaking strategy. The proposed ionically conductive double network hydrogel is achieved by combining chemically crosslinked polyacrylamide and physically crosslinked gelatin network followed by sodium citrate solution immersing. The obtained hydrogel has a tensile strength of 1.66 MPa and an elongation of 849%. The ionically conductive hydrogels can be utilized as both strain and pressure sensors with high sensitivity. Moreover, they can be used as ionic skin to monitor various human movements precisely, demonstrating their promising potential in wearable devices and flexible electronics. Abstract : Ionically conductive polyacrylamide/gelatin hydrogels with high strength, fast self‐recovery, and low residual strains are developed through a facile soaking strategy in a citrate solution. The ionically conductive hydrogels with high strain and pressure sensitivity are further integrated as strain and pressure sensors to monitor various human movements including joint bending, speaking, walking, and jumping .